UPAYA MENGEMBANGKAN MENTAL SANTRI MELALUI KEGIATAN MUHADLOROH DI PONDOK PESANTREN RAUDLATUL ULUM 1 - Moch Umar Faroq Al Farizi1; Muhammad Husni (JURNAL ILMIAH RESEARCH STUDENT, 2026)
. This study aims to develop students' mental capacity through muhadhoroh activities at Pondok Pesantren Raudlatul Ulum 1. Muhadhoroh is a public speaking practice that includes speeches, lectures, sermons, and master of ceremony roles. The method used is participatory mentoring with stages of initial observation, activity planning, routine muhadhoroh implementation, and evaluation and reflection. The results show that structured and routine muhadhoroh activities can increase self-confidence, courage to speak in public, and students' communication skills. This activity also shapes students' mentality to be more prepared to become missionary cadres and community leaders. The outcomes of this activity are increased student self-confidence, the formation of more structured muhadhoroh activities, and a community service report.